Elevated Serum S100B Protein and Neuron-Specific Enolase Levels in Carbon Monoxide Poisoning - Yardan, T.; Çevik, Y.; Dönderici, O.; Kavalcı, C.; Yilmaz, F.M.; Yilmaz, G.; Vural, K. (W B Saunders Co-Elsevier Inc, 2009)
Objective: Carbon monoxide (CO) poisoning causes cerebral and generalized hypoxia. This study aimed to assess the possible use of serum glial marker S100B protein and neuron-specific enolase (NSE) as biochemical markers of hypoxic brain damage in acute CO poisoning. Methods: Patients with acute CO poisoning admitted to the ED of 2 training hospitals (Ankara, Turkey) were included in this cross-sectional study. Serum levels of S100B and NSE were measured on admission. The patients were divided into 2 groups (unconscious and conscious). Twenty healthy adults were included in the study to serve as controls. Results: A total of 70 patients poisoned by CO (mean age ± SD, 36.6 ± 16.3 years; 64.3% women) were enrolled. Although S100B concentrations were higher in patients than in the control group (P = .018), no significant difference was determined between patient and control groups with respect to NSE concentrations (P = .801). A positive correlation was noted between levels of S100B and NSE (r = 0.388; P = .001). The S100B and NSE values were higher in unconscious patients than in the control group (P = .002 and P = .013, respectively). Furthermore, S100B and NSE values were higher in unconscious vs unconscious patients (P = .047 and P = .005, respectively). Conclusion: Elevated serum S100B and NSE levels were associated with loss of consciousness in CO poisoning in this series of patients. Serum S100B and NSE may be useful markers in the assessment of clinical status in CO poisoning. © 2009 Elsevier Inc. All rights reserved.